Mongolian Part of the Transboundary Sailugem Natural Plague Focus in 2017. Communication 1. Epizootic condition - V. M. Korzun; S. V. Balakhonov; A. V. Denisov; M. B. Yarygina; E. N. Rozhdestvensky; D. E. Abibulaev; V. V. Shefer; S. A. Kosilko; D. Otgonbayar; M. Baigalmaa; L. Orgilbayar; Ch. Urzhikh; et al. (Проблемы особо опасных инфекций, 2018)
Objective – estimation of current epizootic condition of Mongolian part of transboundary Sailugem natural plague focus. Materials and methods. Epizootiological survey was performed for the area of 2335 km2, 277 mammals and 516 ectoparasites were investigated for plague. Results and conclusions. Eight Yersinia pestis subsp. pestis strains were isolated, including 7 strains – from grey marmots (6 – from the remains of meals of predatory birds, 1 from a corpse) and 1 – from long-tailed souslik (corpse). Y. pestis DNA was detected in 52 objects. Serological samples showed 40 positive results. Epizootic manifestations, confirmed by isolation of Y. pestis cultures, detection of plague microbe DNA, and positive serological results, were observed across the area of 1611 km2 covering 69 % of the inspected territory. Epizootic results indicated high infection rate of mass mammal species and first of all grey marmots. The data demonstrated that the extended plague epizooty caused by Y. pestis of the main subspecies occurred in the inspected territory in the carrier settlements. For the first time the circulation of Y. pestis subsp. pestis was registered in the Mongolian part of the transboundary Sailugem focus.